2015
DOI: 10.4081/itjm.2015.554
|View full text |Cite
|
Sign up to set email alerts
|

The heart failure in Internal Medicine in Tuscany: the SMIT Study

Abstract: The incidence and prevalence associated with the growing age of population have made heart failure (HF) a new epidemic. In Italy most of HF patients are admitted to Internal Medicine Departments (IMD). We conducted a 30-day cross-sectional study involving patients with HF admitted to IMD of Tuscany. The aim of the study was to provide an updated snapshot of in-hospital management of HF in Tuscany and to analyze the differences in relation to the most recent guidelines. We have recruited 770 patients (M=45.4%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…These features are confirmed in another recent Italian study on 770 patients with HF observed in Internal Medicine wards, showing a mean age of 82.5 years. 23 Results of the present study agree with the above-mentioned data (mean age of 76.9 years, with 76% of patients older than 70 years). In a subgroup analysis in our whole series (Table 3), we observed several statistically significant age-differences as regards etiological factors, comorbidity and cardiac rhythm; all the same, some medications such as β-blockers, oral anticoagulant and double antiplatelet agents were significantly less frequent assumed in older patients.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These features are confirmed in another recent Italian study on 770 patients with HF observed in Internal Medicine wards, showing a mean age of 82.5 years. 23 Results of the present study agree with the above-mentioned data (mean age of 76.9 years, with 76% of patients older than 70 years). In a subgroup analysis in our whole series (Table 3), we observed several statistically significant age-differences as regards etiological factors, comorbidity and cardiac rhythm; all the same, some medications such as β-blockers, oral anticoagulant and double antiplatelet agents were significantly less frequent assumed in older patients.…”
Section: Discussionsupporting
confidence: 83%
“…25 Various comorbidities usually coexist in elderly patients and contribute to the development of HF, end stage heart disease and death ant this negative prognostic impact of concomitant diseases has been documented in several studies. [22][23][24]26 In the present survey we have observed that 64.9% patients had more than two chronic conditions, with a higher, but non-significant, prevalence in women. These results are quite similar to that of the above-mentioned Italian study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…18 In the SMIT study (an observational study performed on 770 patients admitted for HF to 32 departments of internal medicine in Tuscany, a region of central Italy), there was a female prevalence (F 55%, M 45%) and an average age of 82.5 years; 71.5% had at least three comorbidities, and 40.2% at least four comorbidities, in particular arterial hypertension, renal impairment, atrial fibrillation, COPD, and diabetes mellitus. 19 Preserved left systolic ventricular function is more frequent in internal medicine wards than in cardiology wards. In the TEMISTOCLE study, 40.8% of patients admitted to internal medicine had ejection fraction (EF) >40%, vs 28.4% of those admitted to cardiology.…”
Section: Heart Failure In Internal Medicine: Patients' Characteristicsmentioning
confidence: 99%
“…42 Cognitive defects were found in 30% of HF patients admitted to internal medicine wards. 19 Neprilysin is responsible for the breakdown of peptides, including amyloid-beta peptide. It has been hypothesized that inhibiting neprilysin may elevate levels of this peptide in the brain.…”
Section: Angiotensin II Receptor Neprilysin Inhibitor and Alzheimer'smentioning
confidence: 99%